Case fatality rate and associated factors in patients with 22q11 microdeletion syndrome: a retrospective cohort study. Issue 11 (6th November 2014) - Repetto, Gabriela M; Guzmán, M Luisa; Delgado, Iris; Loyola, Hugo; Palomares, Mirta; Lay-Son, Guillermo; Vial, Cecilia; Benavides, Felipe; Espinoza, Karena; Alvarez, Patricia
Abstract : Objective: Chromosome 22q11.2 deletion is the most commonly occurring known microdeletion syndrome. Deaths related to the syndrome have been reported, but the magnitude of death has not been quantified. This study evaluated the deletion's impact on survival and its clinical manifestations in a large cohort of Chilean patients. Design: Demographic and clinical data of individuals with 22q11 deletions diagnosed between 1998 and 2013 were collected from medical records and death certificates. Case fatality rate was calculated and compared with national vital statistics. OR with 95% CI analysis was used to assess the association between clinical manifestations and death. Setting: Genetic services in tertiary care centres in Chile, following patients with 22q11.2 deletion. Outcomes: Fatality rate and associated factors. Results: 59 of 419 patients (14.1%) died during the study period at a median of 3.4 months (range 0 to 32 years of age). Factors associated with death included congenital heart disease (OR 5.27; 95% CI 2.06 to 13.99; p<0.0001), hypocalcaemia (OR 4.27; 95% CI 1.67 to 11.15; p<0.002) and airway malacia (OR 13.37; 95% CI 1.19 to 110.51; p<0.002). Patients with deletions and defects such as tetralogy of Fallot with or without pulmonary atraesia, truncus arteriosus or ventricular septal defect, had a 2.6-fold to 4.6-fold higher death rate compared with nationwide reports for the same types of defects. Conclusions: In this cohort, we observed a death rate of 14.1%, implying that one in seven patients with 22q11 deletion died during the study period. Significant associations with cardiac defects, hypocalcaemia and airway malacia were observed. Furthermore, the death risk in patients with 22q11 deletion and cardiac defects exceeded the global figures observed in Chile for infants with structurally similar but apparently isolated anomalies. These observations indicate a need to identify patients who may require specific perioperative management to improve survival.